MASALAH KESEHATAN WISATAWAN DI BALI: STUDI TENTANG DAMPAK “BALI BELLY” TERHADAP PENGALAMAN DAN CITRA DESTINASI - Antara, Ida Bagus Ketut Soma; Suwintari, I Gusti Ayu Eka; Arianty, Anak Agung Ayu Arun Suw (Penerbit Lafadz Jaya, 2025)
Bali Belly, a digestive disorder commonly experienced by tourists in Bali, poses a significant challenge to the island’s reputation as a global tourism destination. This study aims to explore how Bali Belly affects tourist experiences and the image of Bali as a travel destination. Employing a qualitative approach with a phenomenological method, this research delves into the subjective perceptions and lived experiences of affected international tourists. Data were collected through in-depth interviews, participatory observations in high-incidence areas (such as Kuta, Seminyak, Canggu, and Ubud), and content analysis of online reviews. The findings reveal that Bali Belly not only disrupts tourists’ physical comfort and activity schedules but also triggers negative perceptions widely disseminated through social media and travel platforms. Major risk factors include poor sanitation, low hygiene standards in food establishments, and a lack of health awareness among both tourists and local businesses. Nevertheless, many visitors continue to view Bali positively due to its natural beauty and rich cultural heritage. This study highlights the importance of improving sanitation infrastructure, enhancing hygiene education, and fostering multi-stakeholder collaboration to manage health risks and sustain Bali’s competitiveness in the global tourism industry.